2013
DOI: 10.1038/gim.2012.145
|View full text |Cite
|
Sign up to set email alerts
|

Autism genetic testing: a qualitative study of awareness, attitudes, and experiences among parents of children with autism spectrum disorders

Abstract: Purpose:The goal of this first-of-its-kind qualitative study was to examine the awareness, attitudes, and experiences among parents of autistic children regarding autism genetic testing. Methods:We conducted in-depth, individual, and semistructured interviews with 42 parents of autistic children with diverse racial/ethnic backgrounds. All interviews were audio-taped, transcribed, and coded into major themes and subthemes.Results: Approximately one-quarter of participants had two or more autistic children, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
98
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(124 citation statements)
references
References 35 publications
19
98
1
Order By: Relevance
“…The intention of parents within our study to have their children receive testing was found relatively high at 84.3%, which suggests that majority of participants are likely to consider having their ASD-affected child undergo CMA. This number is consistent with existing findings about the level of parent interest toward ASD genetic testing [12,13,21,22,42]. For instance, Vande Wydeven et al [24] found parental interest in utilizing genetic services at 90%.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The intention of parents within our study to have their children receive testing was found relatively high at 84.3%, which suggests that majority of participants are likely to consider having their ASD-affected child undergo CMA. This number is consistent with existing findings about the level of parent interest toward ASD genetic testing [12,13,21,22,42]. For instance, Vande Wydeven et al [24] found parental interest in utilizing genetic services at 90%.…”
Section: Discussionsupporting
confidence: 88%
“…Most significantly, parental intention toward CMA genetic testing of their children within this study was associated with the prospect of contributing to research. This highlights that this factor, which has been consistently described in qualitative studies on parent perception about CMA could indeed be predictive of test intention [21,[41][42][43]. The finding that increase in intention to test is associated with desire to support research corroborates existing data with similar findings from quantitative studies about genetic testing intention [33][34][35].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations